2021
DOI: 10.3390/plants10122726
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Trait Modeling of Field-Grown Switchgrass (Panicum virgatum) Using UAV-Based Imagery

Abstract: Unmanned aerial vehicles (UAVs) provide an intermediate scale of spatial and spectral data collection that yields increased accuracy and consistency in data collection for morphological and physiological traits than satellites and expanded flexibility and high-throughput compared to ground-based data collection. In this study, we used UAV-based remote sensing for automated phenotyping of field-grown switchgrass (Panicum virgatum), a leading bioenergy feedstock. Using vegetation indices calculated from a UAV-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…A highly diverse panel of 331 switchgrass accessions ( Lovell et al, 2021 ) was planted in May 2019 in a 75.2 m × 122.5 m dimension at The University of Tennessee Plant Sciences Unit of the East Tennessee Research and Education Center (ETREC) (latitude: 35°54′11.14″N; longitude: 83°57′33.31″W; and elevation: 255.7 m.). Planting details and experimental design can be found in Li et al (2020) and Xu et al (2021) . Briefly, the 331 accessions were planted under two nitrogen (N) fertility treatments: one with moderate nitrogen (135 kg of N ha –1 ), while the other with low (0 kg of N ha –1 ) supplementation in 2019 and 2020.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly diverse panel of 331 switchgrass accessions ( Lovell et al, 2021 ) was planted in May 2019 in a 75.2 m × 122.5 m dimension at The University of Tennessee Plant Sciences Unit of the East Tennessee Research and Education Center (ETREC) (latitude: 35°54′11.14″N; longitude: 83°57′33.31″W; and elevation: 255.7 m.). Planting details and experimental design can be found in Li et al (2020) and Xu et al (2021) . Briefly, the 331 accessions were planted under two nitrogen (N) fertility treatments: one with moderate nitrogen (135 kg of N ha –1 ), while the other with low (0 kg of N ha –1 ) supplementation in 2019 and 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The detail of the nitrogen quantification was previously described in Xu et al (2021) . Briefly, nitrogen content of the aboveground biomass was measured via near-infrared spectroscopy (NIRS) using a FOSS 6500 NIR system (Silver Spring, MD, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The NDVI and the NDRE are commonly used as proxies for vegetation quantity and quality [50], and the NDRE, in particular, has been used to model biomass in rangelands with significant spatial and temporal variability [51]. Furthermore, scientists [52] have also found that NDRE can outperform the NDVI to model the nitrogen content for switchgrass (Panicum virgatum). And, concordant with our results, this study found that some traits could be modeled using simple linear models, but other traits (N content) required nonlinear approaches.…”
Section: Differences Across Model Structures-how Multispectral Datase...mentioning
confidence: 99%